Unmodified cellulose beads and methods of making same
Through the manufacturing method of unmodified cellulose beads, cellulose microfibers are directly extracted from raw material pulp to form unmodified cellulose beads, which solves the problem of slow popularization of microplastic alternative materials and high environmental load caused by the chemical fiber deficiency process in the prior art, and achieves the effect of taking into account texture and soft focus in cosmetics.
Patent Information
- Application Number
- CN202380050176.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-05-25
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the popularization of alternative materials for microplastics, especially fine resin raw materials with particle size of less than 100 μm, has been slow, and the use of chemical fiber deficiencies has resulted in high environmental load and chemical residues, which limits its wide application in cosmetics and other uses.
By the manufacturing method of unmodified cellulose beads, mercerizing process, depolymerizing process, fiber deficitization process, neutralizing process and drying process are adopted to avoid the use of chemical fiber deficitization process, and cellulose microfibers are directly extracted from raw material pulp to form unmodified cellulose beads.
It realizes unmodified cellulose beads that take into account both texture and flexibility in cosmetics. The average particle size is uniform, the standard deviation is moderate, the Hunter has high whiteness and low yellowness. It is suitable as a substitute material for microplastics, improving the safety and purity of cosmetics.
Smart Images

Figure CN119768438A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to unmodified cellulose beads and methods for making the same. Background Art
[0002] In recent years, the United Nations has proposed international goals for sustainable development called Sustainable Development Goals (SDGs), and one of the environmental issues is to reduce the use of plastics. By reducing the use of petroleum-derived plastics, efforts are being made to address climate change by reducing GHG.
[0003] For example, in cosmetics such as foundation, microplastics (beads) are sometimes used to improve the compatibility with other ingredients, spreadability or touch during use. However, microplastics (beads) are particularly problematic as one of the main causes of severe marine environmental pollution, and efforts are being made to suppress and recycle the amount of microplastics produced.
[0004] Therefore, the market is working on replacing microplastics (beads). However, it is known that the popularization of alternative materials for fine resin raw materials, such as microplastics (beads) with a particle size of 100 μm or less, has not progressed, and despite the increase in demand, the supply is still small.
[0005] In addition, as an alternative raw material for microplastics, cellulose, which is biodegradable among natural raw materials, has attracted attention. Usually, when cellulose is formed, for example, a viscose method is used to chemically modify the cellulose and dissolve it. However, since this process uses chemicals such as organic solvents with high environmental load, there are concerns about the safety of the environment and products. On the other hand, although it is not a dissolving system, cellulose microfibers such as cellulose nanofibers and cellulose microfibers can also be processed into a molded body, which can be processed into beads or films, and is expected to be an alternative raw material for microplastics.
[0006] As methods for producing cellulose microfibers, the following methods can be cited: a method in which cellulose is oxidized in water using a catalyst and the resulting oxidized cellulose is defibrated to obtain a cellulose nanofiber dispersion (see Patent Document 1); or a method in which cellulose is carboxymethylated in a mixed solvent of water and an organic solvent and the resulting carboxymethylated cellulose is defibrated to obtain a nanofiber dispersion of carboxymethylated cellulose having high transparency (see Patent Document 2); a method for producing anion-modified cellulose nanofibers by desalting anion-modified cellulose nanofiber salt by a cation exchange reaction using a cation exchange resin (see Patent Document 3), etc.
[0007] The cellulose microfibers obtained by these production methods are type I cellulose microfibers, and in order to obtain cellulose fibers with a small fiber diameter, chemical defibration and mechanical (physical) defibration are used to obtain chemically modified cellulose. That is, since chemical agents such as organic solvents are used for defibration, there are problems such as the need for a chemical removal step, which complicates the process, and the chemical residues, which makes it impossible to use it for cosmetics, etc., which limits its use, and there are concerns about safety and environmental load due to the use of chemicals.
[0008] In contrast, unmodified cellulose that has not been chemically defibrated does not use chemicals such as organic solvents during defibration, and there is no problem of residual chemicals on the cellulose microfibers after defibration, so it can be expected to be used in a wide range of applications such as cosmetics. In particular, unmodified cellulose beads obtained from unmodified cellulose can serve as an alternative to microplastics used in cosmetics.
[0009] Generally, microplastics used in cosmetics require good texture such as smoothness. It is believed that the fineness and uniformity of the microbead particles affect the texture of the cosmetics containing the microbeads. On the other hand, cosmetics also require soft focus properties such as eliminating dullness, but cosmetics containing microplastics in the past have difficulty in achieving both texture and soft focus. Therefore, as a substitute for microplastics used in cosmetics, the inventors have repeatedly conducted research and improvements on unmodified cellulose beads obtained from unmodified cellulose. As a result, unmodified cellulose beads and a method for producing the same that achieve both texture and soft focus properties suitable for use in cosmetics were successfully invented.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2008-001728
[0013] Patent Document 2: Japanese Patent Application Publication No. 2019-99758
[0014] Patent Document 3: International Publication No. 2019 / 059079 Summary of the invention
[0015] Problems to be solved by the invention
[0016] The present invention has been made in view of the above-mentioned points, and provides unmodified cellulose beads that achieve both a texture suitable for use in cosmetics and a soft-focus property, and a method for producing the same.
[0017] Means for solving problems
[0018] That is, the invention of claim 1 relates to unmodified cellulose beads, which are unmodified cellulose beads formulated in cosmetics, and the unmodified cellulose beads are characterized in that the average particle diameter (D50) is 1 to 20 μm, the average particle diameter (D10) is 4.0 μm or less, the average particle diameter (D20) is 6.0 μm or less, the average particle diameter (D90) is 30.0 μm or less, and the value (SD / D50) obtained by dividing the standard deviation (SD) of the average particle diameter by the average particle diameter (D50) is 0.4 to 1.5.
[0019] The invention of claim 2 relates to the unmodified cellulose beads according to claim 1, which are produced from raw pulp without undergoing a defibration step by chemical defibration.
[0020] The invention of claim 3 relates to the unmodified cellulose beads according to claim 2 , which have a Hunter whiteness (W value) of 85 or more and a Hunter yellowness (YI value) of 20 or less.
[0021] The invention of claim 4 relates to the unmodified cellulose beads according to claim 1, wherein a dispersion prepared by dispersing 0.05 wt% of the unmodified cellulose beads in 50% of trimethylsilicic acid and 50% of cyclopentasiloxane has a haze value of 50% or more.
[0022] The invention of claim 5 relates to a method for producing unmodified cellulose beads, which is the method for producing unmodified cellulose beads as described in claim 1, and the method is characterized in that it has the following steps: a defibration step, in which alkali metal hydroxide is added to the raw cellulose obtained through the mercerization step and the depolymerization step in a total concentration of 2.5 to 17.5% to perform defibration to obtain cellulose microfibers; a neutralization step, in which the cellulose microfibers are neutralized with an acid; and a drying step, in which the neutralized cellulose microfibers are spray-dried at an air pressure of 0.025 to 0.6 MPa; the mercerization step is a mercerization step in which cellulose is mercerized to obtain mercerized cellulose; and the depolymerization step is a depolymerization step in which the degree of polymerization of the mercerized cellulose is reduced to below 760.
[0023] Effects of the Invention
[0024] The unmodified cellulose beads according to the invention of claim 1 are unmodified cellulose beads to be incorporated into cosmetics, wherein the average particle diameter (D50) is 1 to 20 μm, the average particle diameter (D10) is 4.0 μm or less, the average particle diameter (D20) is 6.0 μm or less, the average particle diameter (D90) is 30.0 μm or less, and the value (SD / D50) obtained by dividing the standard deviation (SD) of the average particle diameter by the average particle diameter (D50) is 0.4 to 1.5, thereby achieving both a texture suitable for use in cosmetics and soft focus properties.
[0025] According to the unmodified cellulose beads of the invention of claim 2, in the invention of claim 1, the beads are produced from raw pulp without undergoing a defibration step by chemical defibration, and therefore have improved safety in cosmetic applications.
[0026] According to the unmodified cellulose beads of the invention of claim 3, in the invention of claim 2, the Hunter whiteness (W value) is 85 or more and the Hunter yellowness (YI value) is 20 or less, so that high-purity cellulose beads can be obtained.
[0027] According to the unmodified cellulose beads of the invention of claim 4, in the invention of claim 1, the haze value of a dispersion prepared by dispersing 0.05 wt% of the unmodified cellulose beads in 50% of trimethylsilicic acid and 50% of cyclopentasiloxane is 50% or more, and thus excellent soft focus properties can be obtained.
[0028] The method for producing unmodified cellulose beads according to the invention of claim 5 is the method for producing unmodified cellulose beads according to claim 1, comprising the following steps: a defibration step, in which alkali metal hydroxide is added to the raw cellulose obtained through the mercerization step and the depolymerization step in a total concentration of 2.5 to 17.5% to perform defibration to obtain cellulose microfibers; a neutralization step, in which the cellulose microfibers are neutralized with an acid; and a drying step, in which the neutralized cellulose microfibers are spray-dried at an air pressure of 0.025 to 0.6 MPa; the mercerization step is a mercerization step in which cellulose is mercerized to obtain mercerized cellulose; and the depolymerization step is a depolymerization step in which the degree of polymerization of the mercerized cellulose is reduced to below 760; thereby, unmodified cellulose beads that achieve both a texture suitable for use in cosmetics and soft focus properties can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 : is a schematic process diagram of a method for producing unmodified cellulose beads according to one embodiment of the present invention.
[0030] Figure 2 : This is a graph showing the particle size distribution of Trial Examples 1 to 4.
[0031] Figure 3 : This is a graph showing the particle size distribution of Trial Examples 5 to 7 and Comparative Example 1. DETAILED DESCRIPTION
[0032] The unmodified cellulose beads of the present invention are substances formulated in cosmetics and are used, for example, as an alternative raw material for microplastics (beads). Cellulose beads are formed bodies of cellulose microfibers, and from the viewpoint of texture when added to cosmetics, it is preferred to use type II cellulose microfibers that are softer than type I cellulose microfibers having a high-strength type I crystalline structure. Unmodified cellulose beads are formed bodies of chemically unmodified (unmodified) cellulose microfibers among type II cellulose microfibers, and from the viewpoint of safety in cosmetic applications, those made from raw pulp without undergoing a defibration process using chemical defibration are particularly preferred.
[0033] Pulp is mainly a raw material obtained by crushing wood and removing impurities such as lignin to improve the purity of the cellulose component. In addition, cotton linter pulp is used, which is obtained by removing impurities from cotton to improve the purity of the cellulose component. In addition, pulp is fibrous and therefore has high reactivity with chemicals, and is preferably used as a cellulose raw material. In addition to pulp, animal cellulose such as bacterial cellulose produced by microorganisms can also be used. Furthermore, purified cellulose obtained by refining these raw materials can also be used.
[0034] like Figure 1 As shown, the unmodified cellulose beads of the present invention are obtained by a production method having a mercerization step (S1), a depolymerization step (S2), a defibration step (S3), a neutralization step (S4) and a drying step (S5).
[0035] The mercerization step (S1) is a step of mercerizing cellulose to obtain mercerized cellulose. In the mercerization step, cellulose as a raw material is added to an alkali metal hydroxide such as caustic soda (NaOH), and the cellulose fibers are swollen while being heated and stirred as needed. When cellulose fibers are immersed in an alkali metal hydroxide, they are negatively charged and Coulomb force is generated, and the fibers repel each other and are easily defibrated. As described above, since mercerized cellulose is easily defibrated, the energy in the subsequent defibration step (S3) can be reduced.
[0036] Examples of the alkali metal hydroxide used in the mercerizing step include caustic soda (NaOH), lithium hydroxide, potassium hydroxide, and the like. From the viewpoint of cost, safety, and environmental load, caustic soda is preferably used.
[0037] After the mercerization step (S1), the remaining alkali metal hydroxide is removed as needed. The solid content concentration is appropriately adjusted and the depolymerization step (S2) is performed. The depolymerization step (S2) is a step for reducing the degree of polymerization of the mercerized cellulose obtained by the mercerization step (S1) to less than 760. The mercerized cellulose with adjusted solid content is appropriately crushed, oxidatively decomposed by oxygen in the air and aged to achieve a reduction in the degree of polymerization. At this time, the degree of polymerization is less than 760. If the degree of polymerization of the mercerized cellulose is less than 760, the transparency of the dispersion of the obtained cellulose microfibers can be ensured. In addition, the lower the degree of polymerization of the mercerized cellulose, the easier it is to defibrate the cellulose fibers in the subsequent defibration step.
[0038] The aging of the mercerized cellulose in the depolymerization step (S2) is performed at room temperature or under heating conditions. In order to accelerate the depolymerization rate, it is preferable to use heating conditions to such an extent that the raw material does not dry out. In addition, an aging accelerator such as manganese (II) sulfate that accelerates the aging reaction may be added.
[0039] By going through the mercerization step (S1) and the depolymerization step (S2), a raw material cellulose that can be defibrinated into fine fibers is obtained. By mercerizing the cellulose, the raw material cellulose becomes type II cellulose having a type II crystal structure. Although the strength of type II cellulose is inferior to that of type I cellulose, the cellulose fine fibers obtained by the present invention do not need the strength of type I cellulose because they are used as a substitute for plastics in the fields of cosmetics, etc., so the reduction in strength does not become a problem.
[0040] Then, in the defibration step (S3), an alkali metal hydroxide and a solvent (ion exchange water) are added to the raw cellulose to adjust the total concentration to 2.5 to 17.5%, and defibration is performed. As mentioned above, the alkali metal hydroxide used here includes caustic soda, lithium hydroxide, potassium hydroxide, etc. From the viewpoint of cost and safety, caustic soda is preferably used. The defibration of the raw cellulose is carried out by mechanical (physical) defibration. Mechanical (physical) defibration is carried out by a known method using a homogenizer, a water sprayer, etc. Here, since the raw cellulose is swelled by mercerization to form a state that is easy to defibrate, and the degree of polymerization is reduced by the depolymerization step, it can be easily defibrated even without applying high pressure, which is also meaningful in terms of equipment.
[0041] When the concentration of the alkali metal hydroxide is lower than 2.5%, the swelling of the cellulose becomes insufficient, and it may be difficult to defibrate. In addition, when the concentration of the alkali metal hydroxide is higher than 17.5%, the salt concentration becomes high, and the cellulose fibers are easily agglomerated, so it may be difficult to defibrate. When the alkali metal hydroxide deviates from this range and the defibration is insufficient, undefibrated fibers remain in the dispersion of the obtained cellulose microfibers, the transparency is reduced, and the uniformity is insufficient, so that fiber-shaped objects are mixed in the cellulose beads, or the surface state of the cellulose beads becomes rough, resulting in a defective product.
[0042] Defibrination can be performed in several times. For example, after pre-defibration using a mixer, a homogenizer can be used for main defibration, thereby producing uniform cellulose microfibers with a small fiber diameter. In addition, pre-defibration can avoid undesirable situations such as clogging of the defibration device by the raw material cellulose. Pre-defibration can be performed by a mixer, a homogenizer, etc., by a known method. The defibration of cellulose microfibers only requires the average fiber diameter to be defibrated to a size of nanometers to hundreds of nanometers. If it is made to be about 2 to 800 nm, more preferably less than 100 nm, the transparency of the dispersion of cellulose microfibers is improved, and the processing suitability of cellulose beads becomes good.
[0043] The cellulose microfibers obtained in the fibrillation step (S3) are neutralized with an acid in the neutralization step (S4). The cellulose microfibers obtained in the fibrillation step are strongly alkaline and therefore need to be neutralized. Examples of the acid used include sulfuric acid, hydrochloric acid, lactic acid, and the like. The neutralized cellulose microfibers are appropriately washed and defibrated again to obtain type II unmodified cellulose microfibers.
[0044] The drying step (S5) is a step of spray-drying the dispersion of cellulose microfibers obtained in the neutralization step (S4) to form unmodified cellulose beads. The dispersion of cellulose microfibers is agglomerated while being dried by spray drying and formed into granules (beads). The condition for spray drying is an air pressure of 0.025 to 0.6 MPa. If the air pressure of spray drying is insufficient, the cellulose microfibers will not be micronized, the particle size will increase, and the physical properties and texture will deteriorate. In addition, when the air pressure is higher than 0.6 MPa, the air generating device will become too large and unrealistic.
[0045] In addition, in the method for producing unmodified cellulose beads of the present invention, a collection step (S6) is performed after the drying step (S5) as needed. The collection step (S6) is a step of removing unnecessary particles from the cellulose beads formed in the drying step (S5) and recovering cellulose beads with suitable particles. The collection means is not particularly limited as long as suitable particles can be recovered. For example, the collection can be performed by using a known collection means such as a bag filter or a cyclone dust collector. The unmodified cellulose beads obtained in this way can reduce the use of drugs with high environmental load compared to conventional cellulose beads.
[0046] The average particle diameter (D50) of the cumulative value of 50%, the average particle diameter (D10) of the cumulative value of 10%, the average particle diameter (D20) of the cumulative value of 20%, the average particle diameter (D90) of the cumulative value, and the value obtained by dividing the standard deviation (SD) of the average particle diameter by the average particle diameter (D50) (CV value: SD / D50) in the particle size distribution of the unmodified cellulose beads obtained by the production method of the present invention are defined as follows. It should be noted that the average particle diameter (D50) is the median diameter (center diameter), and the average particle diameter (D10), (D20), (D90) and the CV value (SD / D50) show the tendency of the particle size distribution. In particular, the CV value (SD / D50) is an index indicating the uniformity of the particle diameter, and the smaller the value, the more uniform the particle diameter.
[0047] The average particle diameter (D50) of the cumulative value of 50% in the particle size distribution is 1 to 20 μm, more preferably 2.5 to 10 μm. The average particle diameter (D10) of the cumulative value of 10% is 4.0 μm or less, more preferably 3.0 μm or less. The average particle diameter (D20) of the cumulative value of 20% is 6.0 μm or less, more preferably 4.5 μm or less. The average particle diameter (D90) of the cumulative value of 90% is 30.0 μm or less, more preferably 20.0 μm or less. The CV value (SD / D50) is 0.4 to 1.5, more preferably 0.5 to 1.0.
[0048] The unmodified cellulose beads of the present invention are particles having a median diameter (D50) of 1 to 20 μm and a D90 of 30.0 μm or less, and contain a large amount of microparticles having a D10 of 4.0 μm or less and a D20 of 6.0 μm or less, and have a CV value (SD / D50) of 0.4 to 1.5. As such, the overall particle size is relatively uneven, and a good texture with good smoothness and less roughness and astringency can be obtained.
[0049] In addition, the unmodified cellulose beads have excellent soft focus properties. Soft focus properties require a high light diffusion effect, but it is known that in cellulose beads, the smaller the particle size, the higher the haze value, and there is a tendency to obtain a large light diffusion effect. The unmodified cellulose beads of the present invention contain a large number of fine particles as described above, so the light diffusion effect is high and excellent soft focus properties can be obtained. Specifically, the haze value of the dispersion obtained by dispersing 0.05 weight% of unmodified cellulose beads in 50% trimethylsilicic acid and 50% cyclopentasiloxane is 50% or more, and more preferably 60% or more. Therefore, in the unmodified cellulose beads of the present invention, both texture and soft focus properties can be achieved.
[0050] Furthermore, the unmodified cellulose beads have a higher purity than the conventional cellulose beads. Whiteness is used as an indicator of the purity of the cellulose beads. Conventional cellulose beads are made, for example, from viscose obtained by chemically modifying cellulose, but the viscose contains byproducts such as sulfur compounds (sodium trithiocarbonate, etc.) and is colored yellow. Since the sulfur compounds (sodium trithiocarbonate, etc.) remain in the cellulose after manufacture, the cellulose becomes a slightly yellowish substance, and the whiteness of the powder deteriorates. On the other hand, the unmodified cellulose beads of the present invention do not use chemicals (not chemically modified), so there is no influence of byproducts, etc. as in the past, and high whiteness, i.e., high-purity cellulose beads can be obtained. As the preferred purity of the unmodified cellulose beads, the Hunter whiteness (W value) is 85 or more, and the Hunter yellowness (YI value) is 20 or less.
[0051] [Example]
[0052] [Preparation of unmodified cellulose beads]
[0053] Regarding the unmodified cellulose beads of Trial Examples 1 to 7, Figure 1 The process diagram of was produced under the following conditions. In Comparative Example 1, commercially available cellulose beads (Daito Chemical Industry Co., Ltd.: cellulose "CELLOBEAD SD-10") were used.
[0054] <Trial Example 1>
[0055] 18 wt% caustic soda is heated to 50°C, pulp is added to make it 2 wt%, stirred until it becomes a slurry, and mercerized (mercerization process). Then, the remaining caustic soda is removed and the solid content is adjusted to 33 wt%. Aging treatment is carried out at 50°C to reduce the degree of polymerization of mercerized cellulose to below 760 to obtain raw cellulose (depolymerization process). Ion exchange water and caustic soda are added to the treated sample, and fiberization is carried out by a homogenizer (manufactured by SMT Co., Ltd.) (fiberization process). 96.0 kg of the prepared slurry is collected and neutralized by adding 20 wt% sulfuric acid while stirring (neutralization process). The neutralized sample is dehydrated at 15 Hz using a centrifugal washer (manufactured by Matsumoto Machinery Manufacturing Co., Ltd.), and 5 L / min of ion exchange water is sprayed for 30 minutes for cleaning. After adding ion exchange water to the washed sample in a total weight of 96.0 kg, the sample was defibrated again using a homogenizer (manufactured by SMT Co., Ltd.) to obtain a dispersion of type II unmodified cellulose microfibers. This sample was spray-dried (drying process) using a spray dryer (manufactured by Okawara Chemical Industry Co., Ltd.) at an air pressure of 0.25 MPa (processing capacity 75 kg / hr). The particles were collected by collecting dust using a cyclone dust collector (manufactured by Okawara Chemical Industry Co., Ltd.), and then recovered from a bag filter (manufactured by Okawara Chemical Industry Co., Ltd.) (collection process) to obtain unmodified cellulose beads of trial example 1.
[0056] <Trial Example 2>
[0057] 18 wt% caustic soda is heated to 50°C, pulp is added to make it 2 wt%, stirred until it becomes a slurry, and mercerized (mercerization process). Then, the remaining caustic soda is removed and the solid content is adjusted to 33 wt%. Aging treatment is carried out at 50°C to reduce the degree of polymerization of mercerized cellulose to below 760 to obtain raw cellulose (depolymerization process). Ion exchange water and caustic soda are added to the treated sample, and fiberization is carried out by a homogenizer (manufactured by SMT Co., Ltd.) (fiberization process). 96.0 kg of the prepared slurry is collected and neutralized by adding 20 wt% sulfuric acid while stirring (neutralization process). The neutralized sample is dehydrated at 15 Hz using a centrifugal washer (manufactured by Matsumoto Machinery Manufacturing Co., Ltd.), and 5 L / min of ion exchange water is sprayed for 30 minutes for cleaning. After adding ion exchange water to the washed sample in a total weight of 96.0 kg, the sample was defibrated again using a homogenizer (manufactured by SMT Co., Ltd.) to obtain a dispersion of type II unmodified cellulose microfibers. The sample was spray-dried (drying process) using a spray dryer (manufactured by Okawara Chemical Industry Co., Ltd.) at an air pressure of 0.25 MPa (processing capacity 75 kg / hr). The particles were collected and recovered by a single-point collection using a bag filter (manufactured by Okawara Chemical Industry Co., Ltd.) (collection process), and unmodified cellulose beads of trial production example 2 were obtained.
[0058] <Trial Example 3>
[0059] 18 wt% caustic soda is heated to 50°C, pulp is added to make it 2 wt%, stirred until it becomes a slurry, and mercerized (mercerization process). Then, the remaining caustic soda is removed and the solid content is adjusted to 33 wt%. Aging treatment is carried out at 50°C to reduce the degree of polymerization of mercerized cellulose to below 760 to obtain raw cellulose (depolymerization process). Ion exchange water and caustic soda are added to the treated sample, and fiberization is carried out by a homogenizer (manufactured by SMT Co., Ltd.) (fiberization process). 96.0 kg of the prepared slurry is collected and neutralized by adding 20 wt% sulfuric acid while stirring (neutralization process). The neutralized sample is dehydrated at 15 Hz using a centrifugal washer (manufactured by Matsumoto Machinery Manufacturing Co., Ltd.), and 5 L / min of ion exchange water is sprayed for 30 minutes for cleaning. After adding ion exchange water to the washed sample in a total weight of 96.0 kg, the sample was defibrated again using a homogenizer (manufactured by SMT Co., Ltd.) to obtain a dispersion of type II unmodified cellulose microfibers. The sample was spray dried (drying process) using a spray dryer (manufactured by Okawara Chemical Industry Co., Ltd.) at an air pressure of 0.25 MPa (processing capacity 75 kg / hr). The particles were collected and recovered using a cyclone dust collector (manufactured by Okawara Chemical Industry Co., Ltd.) (collection process), and unmodified cellulose beads of trial production example 3 were obtained.
[0060] <Trial Example 4>
[0061] 18 wt% caustic soda is heated to 50°C, pulp is added to make it 2 wt%, stirred until it becomes a slurry, and mercerized (mercerization process). Then, the remaining caustic soda is removed and the solid content is adjusted to 33 wt%. Aging treatment is carried out at 50°C to reduce the degree of polymerization of mercerized cellulose to below 760 to obtain raw cellulose (depolymerization process). Ion exchange water and caustic soda are added to the treated sample, and fiberization is carried out by a homogenizer (manufactured by SMT Co., Ltd.) (fiberization process). 96.0 kg of the prepared slurry is collected and neutralized by adding 20 wt% sulfuric acid while stirring (neutralization process). The neutralized sample is dehydrated at 15 Hz using a centrifugal washer (manufactured by Matsumoto Machinery Manufacturing Co., Ltd.), and 5 L / min of ion exchange water is sprayed for 30 minutes for cleaning. After adding ion exchange water to the washed sample in a total weight of 96.0 kg, the sample was defibrated again using a homogenizer (manufactured by SMT Co., Ltd.) to obtain a dispersion of type II unmodified cellulose microfibers. The sample was spray dried (drying process) using a spray dryer (manufactured by GF Co., Ltd.) at an air pressure of 0.6 MPa (processing capacity 2.64 kg / hr). The particles were collected and recovered using a bag filter (manufactured by GF Co., Ltd.) (collection process) to obtain unmodified cellulose beads of trial example 4.
[0062] <Trial Example 5>
[0063] 18 wt% caustic soda is heated to 50°C, pulp is added to make it 2 wt%, stirred until it becomes a slurry, and mercerized (mercerization process). Then, the remaining caustic soda is removed and the solid content is adjusted to 33 wt%. Aging treatment is carried out at 50°C to reduce the degree of polymerization of mercerized cellulose to below 760 to obtain raw cellulose (depolymerization process). Ion exchange water and caustic soda are added to the treated sample, and fiberization is carried out by a homogenizer (manufactured by SMT Co., Ltd.) (fiberization process). 96.0 kg of the prepared slurry is collected and neutralized by adding 20 wt% sulfuric acid while stirring (neutralization process). The neutralized sample is dehydrated at 15 Hz using a centrifugal washer (manufactured by Matsumoto Machinery Manufacturing Co., Ltd.), and 5 L / min of ion exchange water is sprayed for 30 minutes for cleaning. After adding ion exchange water to the washed sample in a total weight of 96.0 kg, the sample was defibrated again using a homogenizer (manufactured by SMT Co., Ltd.) to obtain a dispersion of type II unmodified cellulose microfibers. The sample was spray dried (drying process) using a spray dryer (manufactured by GF Co., Ltd.) at an air pressure of 0.06 MPa (processing capacity 2.40 kg / hr). The particles were collected and recovered using a bag filter (manufactured by GF Co., Ltd.) (collection process) to obtain unmodified cellulose beads of trial example 5.
[0064] <Trial Example 6>
[0065] 18 wt% caustic soda is heated to 50°C, pulp is added to make it 2 wt%, stirred until it becomes a slurry, and mercerized (mercerization process). Then, the remaining caustic soda is removed and the solid content is adjusted to 33 wt%. Aging treatment is carried out at 50°C to reduce the degree of polymerization of mercerized cellulose to below 760 to obtain raw cellulose (depolymerization process). Ion exchange water and caustic soda are added to the treated sample, and fiberization is carried out by a homogenizer (manufactured by SMT Co., Ltd.) (fiberization process). 96.0 kg of the prepared slurry is collected and neutralized by adding 20 wt% sulfuric acid while stirring (neutralization process). The neutralized sample is dehydrated at 15 Hz using a centrifugal washer (manufactured by Matsumoto Machinery Manufacturing Co., Ltd.), and 5 L / min of ion exchange water is sprayed for 30 minutes for cleaning. After adding ion exchange water to the washed sample in a total weight of 96.0 kg, the sample was defibrated again using a homogenizer (manufactured by SMT Co., Ltd.) to obtain a dispersion of type II unmodified cellulose microfibers. The sample was spray dried (drying process) using a spray dryer (manufactured by GF Co., Ltd.) at an air pressure of 0.025 MPa (processing capacity 2.40 kg / hr). The particles were collected and recovered using a bag filter (manufactured by GF Co., Ltd.) (collection process) to obtain unmodified cellulose beads of trial example 6.
[0066] <Trial Example 7>
[0067] 18 wt% caustic soda is heated to 50°C, pulp is added to make it 2 wt%, stirred until it becomes a slurry, and mercerized (mercerization process). Then, the remaining caustic soda is removed and the solid content is adjusted to 33 wt%. Aging treatment is carried out at 50°C to reduce the degree of polymerization of mercerized cellulose to below 760 to obtain raw cellulose (depolymerization process). Ion exchange water and caustic soda are added to the treated sample, and fiberization is carried out by a homogenizer (manufactured by SMT Co., Ltd.) (fiberization process). 96.0 kg of the prepared slurry is collected and neutralized by adding 20 wt% sulfuric acid while stirring (neutralization process). The neutralized sample is dehydrated at 15 Hz using a centrifugal washer (manufactured by Matsumoto Machinery Manufacturing Co., Ltd.), and 5 L / min of ion exchange water is sprayed for 30 minutes for cleaning. After adding ion exchange water to the washed sample in a total weight of 96.0 kg, the sample was defibrated again using a homogenizer (manufactured by SMT Co., Ltd.) to obtain a dispersion of type II unmodified cellulose microfibers. The sample was spray-dried (drying process) using a spray dryer (manufactured by GF Co., Ltd.) at an air pressure of 0.02 MPa (processing capacity 2.64 kg / hr). The particles were collected and recovered using a bag filter (manufactured by GF Co., Ltd.) (collection process) to obtain unmodified cellulose beads of trial example 7.
[0068] As performance evaluation of the unmodified cellulose beads of each of Prototype Examples 1 to 7 and Comparative Example 1, the particle size distribution, haze (%), and whiteness were measured, and a sensory test of texture was performed.
[0069] [Particle size distribution]
[0070] About the cellulose beads of Prototype Examples 1 to 7 and Comparative Example 1, the average particle size (μm) was measured according to JIS Z 8825 (2013). Figure 2 , 3 This is a graph showing the particle size distribution of the unmodified cellulose beads of Trial Examples 1 to 7 and Comparative Example 1 obtained by measurement. A laser diffraction / scattering particle size distribution measuring device (MicrotrackBell Co., Ltd.: "MT3200II") was used to measure the average particle size of each cellulose bead. During the measurement, a slurry obtained by mixing each cellulose bead with ion exchange water was first filled into a sample circulator. The slurry was stirred to such an extent that no uneven parts were visually observed immediately before supply. Then, it was supplied to a measuring device, and each measurement parameter was set as follows: the refractive index of ion exchange water was 1.33, the light transmittance of the measured object particles was transmittance, the measuring time was 10 seconds, and the particle size (D10) corresponding to 10% of the cumulative particle size distribution (volume basis), the particle size (D20) corresponding to 20% of the cumulative particle size distribution (volume basis), the particle size (D50) corresponding to 50% of the cumulative particle size distribution (volume basis), the particle size (D90) corresponding to 90% of the cumulative particle size distribution (volume basis), and the standard deviation (SD) of the average particle size were measured respectively.
[0071] [Haze]
[0072] For the cellulose beads of Trial Examples 1 to 7 and Comparative Example 1, a 0.05 mass % dispersion of each cellulose bead was prepared, and the haze (%) was measured according to JIS K7136 (2000). The haze (%) is an index of transparency, and a haze meter (manufactured by Nippon Denshoku Industries: “NDH-4000”) was used. The concentration of the dispersion was adjusted using a 50% trimethylsilicic acid · 50% cyclopentasiloxane solution (manufactured by Shin-Etsu Chemical Co., Ltd.: “KF7312J”), and a glass cuvette (manufactured by Fujiwara Seisakusho Co., Ltd.: “MG-40”) was added to the light path of 1 cm. Zero point measurement was performed by adding a 50% trimethylsilicic acid · 50% cyclopentasiloxane solution to the same glass cuvette. For the cellulose beads of Trial Examples 1 to 7 and Comparative Example 1, the haze was evaluated by evaluating the results of 50% or more as “good (○)” and the results of less than 50% as “unacceptable (×)”.
[0073] [Whiteness]
[0074] The Hunter whiteness (W value) and Hunter yellowness (YI value) of the cellulose beads of Trial Examples 1 to 7 and Comparative Example 1 were calculated in accordance with JIS P 8123. Whiteness is an index of cellulose purity, and the chromaticity coordinates X, Y, and Z specified by CIE (International Commission on Illumination) were obtained by comparison with a standard white plate (X=91.2, Y=96.1, Z=104.5) using a spectrocolorimeter (manufactured by Nippon Denshoku Industries Co., Ltd.: "SE7700"), and the whiteness (W value) and yellowness (YI value) were calculated using the following formula.
[0075] Whiteness (W value) = Z / 1.18
[0076] Yellowness (YI value) = (X-0.98×W / 0.8)×Y
[0077] In the cellulose beads of Trial Examples 1 to 7 and Comparative Example 1, the whiteness was evaluated as "good (0)" when the Hunter whiteness (W value) was 85 or more and the Hunter yellowness (YI value) was 20 or less, and the Hunter whiteness (W value) was less than 85 or the Hunter yellowness (YI value) was greater than 20 as "unacceptable (×)".
[0078] [Functional test]
[0079] The cellulose beads of Trial Examples 1 to 7 and Comparative Example 1 were spread on the skin with fingers, and 10 testers evaluated the smoothness, roughness, and stickiness at this time in 5 levels. For each item, the texture of each item was evaluated by setting the average score of 5.0 to 4.5 as "◎", 4.4 to 3.5 as "○", 3.5 to 2.5 as "△", and 2.4 or less as "×".
[0080] [Comprehensive evaluation]
[0081] The measurement results and test results of the cellulose beads of Prototype Examples 1 to 7 and Prototype Example 1, as well as the judgments thereof, are shown in Tables 1 and 2. In addition, as a comprehensive evaluation, the case where there were two or more "△" or even one "×" in the judgment was regarded as "unacceptable (×)", the case where there was no "×" but even one "△" was regarded as "acceptable (△)", and the judgments above these were regarded as "good (○)".
[0082] [Table 1]
[0083]
[0084] [Table 2]
[0085]
[0086] [Results and Investigation]
[0087] The cellulose beads of Comparative Example 1, which are commercially available, are as follows Figure 3As shown in the figure, the particle size distribution is narrow near the particle size of 10 μm, and the CV value (SD / D50) is 0.28, which shows that the particle size is relatively uniform near about 10 μm. As a result, the texture is good in terms of smoothness and roughness, but the astringency caused by the uniformity of the particle size is strong, and the haze value is low, and the soft focus is insufficient.
[0088] On the other hand, the cellulose beads of Trial Examples 1 to 7 are as follows Figure 2 , 3 As shown, the particle size distribution is relatively flat (lateral expansion graph) compared with Comparative Example 1, and the CV value (SD / D50) is high, and the deviation of the particle size is large, that is, the particle size is relatively non-uniform. For the cellulose beads of Trial Examples 1 to 7, improvement in the astringent feeling is observed compared with the cellulose beads of Comparative Example 1.
[0089] In particular, regarding Trial Examples 1 to 7, the cellulose beads of Trial Examples 1 to 6 showed that not only the astringent feeling but also all the textures including smoothness and roughness were good, and the haze value was high and the soft focus property was excellent. On the other hand, Trial Example 7 showed that the textures in terms of smoothness and roughness were poor, the haze value was low, and the soft focus property was poor.
[0090] Therefore, when comparing Trial Examples 1 to 6 with Comparative Example 1, the cellulose beads of Trial Examples 1 to 6 have a particle size distribution that is closer to a smaller particle size and is flatter than the cellulose beads of Comparative Example 1, and therefore the particles as a whole have a relatively non-uniform particle size and contain a large number of particles (fine particles) that are smaller than those of Comparative Example 1. Conventionally, it has been considered that a relatively uniform particle size (a sharp peak in the particle size distribution) is good, but Trial Examples 1 to 6 show that both texture and soft focus can be achieved by having a non-uniform particle size as a whole and containing a large number of fine particles (a particle size distribution that is closer to a smaller particle size and has a slightly flat peak).
[0091] It should be noted that the cellulose beads of Trial Example 7 contain a large number of particles with a large particle size compared to Comparative Example 1, and show a characteristic that the overall particle size is relatively non-uniform. The cellulose beads of Trial Example 7 have a less astringent feel than Comparative Example 1, but other textures such as smoothness and roughness are deteriorated, and furthermore, the haze is reduced, and the soft focus property is also deteriorated. From the differences between the characteristics of Trial Examples 1 to 6 relative to Comparative Example 1 and the characteristics of Trial Example 7, it can be seen that in order to achieve both texture and soft focus, it is preferred that the particle size of the cellulose beads is non-uniform and that they contain a large number of fine particles.
[0092] In addition, the cellulose beads of Comparative Example 1 are chemically modified cellulose beads, and as can be seen from the Hunter whiteness (W value) and Hunter yellowness (YI value), they tend to be weak in white and strong in yellow. On the other hand, the cellulose beads of Trial Examples 1 to 7 are unmodified cellulose beads, and both Hunter whiteness (W value) and Hunter yellowness (YI value) are good, and therefore they are higher in purity than Comparative Example 1.
[0093] Industrial Applicability
[0094] According to the unmodified cellulose beads and the method for producing the same of the present invention, it is possible to achieve both a texture suitable for cosmetics and soft focus properties. Therefore, it is expected to be a substitute for microplastics, chemically modified cellulose beads, etc. used in conventional cosmetics.
[0095] Explanation of symbols
[0096] S1 Mercerization process
[0097] S2 Depolymerization process
[0098] S3 Defibrination process
[0099] S4 Neutralization process
[0100] S5 Drying process
[0101] S6 Capture process
Claims
1. Unmodified cellulose beads, which are unmodified cellulose beads formulated in cosmetics, wherein the unmodified cellulose beads are characterized in that: The average particle diameter (D50) is 1 to 20 μm. The average particle diameter (D10) is 4.0 μm or less, The average particle diameter (D20) is 6.0 μm or less, The average particle diameter (D90) is 30.0 μm or less, The value (SD / D50) obtained by dividing the standard deviation (SD) of the average particle diameter by the average particle diameter (D50) is 0.4 to 1.
5. 2 . The unmodified cellulose beads according to claim 1 , which are produced from raw pulp without undergoing a defibration step using chemical defibration. 3 . The unmodified cellulose beads according to claim 2 , which have a Hunter whiteness (W value) of 85 or more and a Hunter yellowness (YI value) of 20 or less.
4. The unmodified cellulose beads according to claim 1, wherein The haze value of a dispersion prepared by dispersing 0.05 wt % of unmodified cellulose beads in 50 % of trimethylsilicic acid and 50 % of cyclopentasiloxane is 50 % or more.
5. A method for producing unmodified cellulose beads, which is the method for producing unmodified cellulose beads according to claim 1, characterized in that the method comprises the following steps: A fibrillation step, in which alkali metal hydroxide is added to the raw cellulose obtained through the mercerization step and the depolymerization step in a total concentration of 2.5 to 17.5% to perform fibrillation to obtain cellulose microfibers; A neutralization step of neutralizing the cellulose microfibers with an acid; and In the drying process, the neutralized cellulose microfibers are spray-dried at an air pressure of 0.025 to 0.6 MPa; The mercerization step is a mercerization step of mercerizing cellulose to obtain mercerized cellulose; The depolymerization step is a depolymerization step for reducing the degree of polymerization of the mercerized cellulose to 760 or less.
Citation Information
Patent Citations
Fine cellulose fiber
JP2008001728A
Production method of carboxymethylated cellulose nanofiber
JP2019099758A
Method for producing anionically modified cellulose nanofibers
WO2019059079A1